Factors Human Resource Development Public Organization - Fajar Rahmanto; Ulung Pribadi (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
Human resources are the main assets in the organization, so the procedures needed for proper management and development. This paper aims to find the factors that influence the improvement of human resources in public organizations. This paper uses qualitative research with interviews and documentation of data collection techniques. Then, analysis techniques using Nvivo 12 plus software with features exploring crosstab queries and cluster analysis features. The results showed that employee performance (22.92%) and compensation (14.58%) had a positive effect, but were not significant for the development of public organization human resource. In contrast, the training had a positive impact (62.50%) and was vital for the development of the human resource organization of the Sleman District Education Office. The training is the most significant factor influencing the development of public organization human resource in the Sleman District Education Office, while employee performance and compensation has an effect on human resource development but the level of influence is not too significant. In conclusions, human resource development in public organizations was significantly influenced by training of employees, then employee performance and compensation